An adaptive constant current and voltage mode P&O-based Maximum Power Point Tracking controller IC using 0.5-μm HV CMOS. (December 2021) - Wang, Chua-Chin; Jose, Oliver Lexter July A.; Su, Po-Kai; Tolentino, Lean Karlo S.; Sangalang, Ralph Gerard B.; Velasco, Jessica S.; Lee, Tzung-Je
Abstract: Photovoltaic (PV) energy harvesting has been widely used in the application of energy storage for battery charging. The more solar energy effectively harvested by the harvesting circuit, the more efficient charging will take place. Many papers used different MPPT methods that enhance PV harvesting that require ADC and MCU which is costly and also requires a long period of tracking. A high-voltage energy harvesting circuit with adaptive constant current (ACC), constant voltage (CV), and maximum power tracking (MPPT) control for 20V/ 5 W solar panels is proposed to carry out the constant current charging (CC) and constant voltage (CV) charging modes of lithium-ion batteries when the solar panel's maximum power point changes. Pulse width modulation (PWM) and pulse frequency modulation (PFM) are implemented under different light intensity conditions to improve the efficiency. The ACC mode controlled by perturb-and-observe (PBO) MPPT algorithm improved the efficiency during insufficient light source or low battery power. When the battery is fully charged, the over-charging damage is prevented to the lithium-ion battery when CV mode is activated. TSMC 0.5- μ m UHV process is used to fabricate the energy harvesting circuit. For the photocurrent range of 0.1 A to 0.3 A, this design achieved a peak efficiency of 98%. Graphical abstract: Highlights: MPPT Controller IC using Perturb and Observe Method. Implemented on a single chip using 0.5 μ m HV CMOS process. Can operate at an input up to 20 V. Output voltage range of 3.6 V to 4.2 V with overcharge protection. Peak efficiency of 98% with 5 W throughput and 20 mW power consumption.